1979
DOI: 10.2307/1319539
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Descriptive Social Reinforcement on Creative Responses in Children's Easel Painting

Abstract: This thesis has been approved on the date shown below: / JEAN RUSH ssistant Professor of Art ACKNOWLEDGMENTS Many people assisted in-the completion of this, research. The author, expresses her sincere appreciation to Dr. Jean. Rush, who served as major advisor and chairperson of the thesis committee. Appreciation is also extended to Dr. Dale Fitzner and Dr. Robert Cardinale who also served on the thesis committee and assisted in my program of study, I also extend gratitude to Wendy, Regine, Bobby, and Joey, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We also excluded studies that reported only team- or organizational-level data because we were concerned with rewards' effects on individual performance. Considering our definition of creativity as involving original and useful production, we excluded studies or study conditions that (a) used self-reported measures of creativity because their validity as measures of performance is not well established (Kurtzberg, 2005); (b) used measures of creative performance that were not consistent with our definition of creativity as involving novelty, such as tests of convergent thinking (e.g., the Remote Association Test) and insight problems (e.g., the Maier coat rack problem or the Duncker candle task) because these measures have close-ended, single solutions; (c) used measures of creativity such as tests of closure (e.g., the Gestalt Completion Test), projective tests of creativity (e.g., the House–Tree–Person test), and word association tests because these measures do not involve any consideration of the aesthetic or practical value of the responses; (d) provided behavioral modeling or creativity training because, as pointed out by an anonymous reviewer, these studies may provide information that renders tasks noncreative (i.e., Cepe-Thomas, 1982; Glover, 1973; Glover & Sautter, 1977; Mendelson, 1973; and one study condition in Hennessey et al, 1989, and Gallman, 1973); or (e) gave highly descriptive feedback (e.g., specific behavioral information) to participants on their prior or current performance on the same type of task they were evaluated on or one that provided instructions that may have simplified the task (e.g., specific information about how creativity is evaluated), because, as pointed out by an anonymous reviewer, such information may simplify the task and render the output noncreative (i.e., Chambers, Goldman, & Kovesdy, 1977; Fallon & Goetz, 1975; Glover, 1973, 1979; Goetz, 1981; Kratochwill, Rush, & Kratochwill, 1979; Lane, Friedman, Goetz, & Pinkston, 1982; Rosen, 1979). Lastly, we excluded studies that did not report enough information to calculate an effect size ( k = 16).…”
Section: Methodsmentioning
confidence: 99%
“…We also excluded studies that reported only team- or organizational-level data because we were concerned with rewards' effects on individual performance. Considering our definition of creativity as involving original and useful production, we excluded studies or study conditions that (a) used self-reported measures of creativity because their validity as measures of performance is not well established (Kurtzberg, 2005); (b) used measures of creative performance that were not consistent with our definition of creativity as involving novelty, such as tests of convergent thinking (e.g., the Remote Association Test) and insight problems (e.g., the Maier coat rack problem or the Duncker candle task) because these measures have close-ended, single solutions; (c) used measures of creativity such as tests of closure (e.g., the Gestalt Completion Test), projective tests of creativity (e.g., the House–Tree–Person test), and word association tests because these measures do not involve any consideration of the aesthetic or practical value of the responses; (d) provided behavioral modeling or creativity training because, as pointed out by an anonymous reviewer, these studies may provide information that renders tasks noncreative (i.e., Cepe-Thomas, 1982; Glover, 1973; Glover & Sautter, 1977; Mendelson, 1973; and one study condition in Hennessey et al, 1989, and Gallman, 1973); or (e) gave highly descriptive feedback (e.g., specific behavioral information) to participants on their prior or current performance on the same type of task they were evaluated on or one that provided instructions that may have simplified the task (e.g., specific information about how creativity is evaluated), because, as pointed out by an anonymous reviewer, such information may simplify the task and render the output noncreative (i.e., Chambers, Goldman, & Kovesdy, 1977; Fallon & Goetz, 1975; Glover, 1973, 1979; Goetz, 1981; Kratochwill, Rush, & Kratochwill, 1979; Lane, Friedman, Goetz, & Pinkston, 1982; Rosen, 1979). Lastly, we excluded studies that did not report enough information to calculate an effect size ( k = 16).…”
Section: Methodsmentioning
confidence: 99%
“…First, research suggests that promoting creative expression through play fosters independence and problem solving in young children (Goetz, 1981 ;Goetz & Baer, 1973 ;Holman, Goetz, & Baer, 1977 ;Ryan & Winston, 1978 ). Teaching children to increase their creative expression during block building (Goetz, 1981 ;Goetz & Baer, 1973 ), unstructured play (Moran, Sawyers, & Moore, 1988 ), and easel painting (Goetz & Salmonson, 1972 ;Kratochwill, Rush, & Kratochwill, 1979 ;Ryan & Winston, 1978 ) can be benefi cial for learning and development in other domains. Creativity in block play, in particular, has been shown to predict academic achievement.…”
Section: Benefi Ts Of Playmentioning
confidence: 99%
“…Early On Scholarly Oblivion, Institutional Amnesia, and Erasure of Research History conducted in the '70s and '80s on students' understanding of art history, art criticism, and aesthetics (among many others are Ecker, 1974;Erickson 1977Erickson , 1979Erickson , 1983Erickson , 1985Gray, 1974;Johansen, 1979) was translated by methods textbooks and many art teachers and teacher educators into a curricular move away from reliance on young people's autonomous expressive ideas as authentic creators of art, and toward teacherdirected modeling of children's art production based on the visual styles and conceptual themes of adult artists from the past. In doing so, the field did not build upon-it instead rejected-its comprehensive scholarship on children's artistic development and creative studio practice (in addition to the large body of research on creativity in young people's studio practice from the '50s and '60s, see Abrahamson, 1972;Beittel, 1978;Korzenik, 1976;Kratochwill, Rush, & Kratochwill, 1979;Packard, 1973). The DBAE movement as a whole deliberately discounted and ignored this earlier research, as exemplified here by Hamblen (1988): "In a DBAE curriculum, the emphasis is on learning art content, research in art education-much of it reflective of a positivistic worldview 20 that sparked an uncomfortable dissonance between experiments and measurements on one hand and idiosyncratic creative practice on the other-was not without its critics.…”
Section: Rethinking a Literaturementioning
confidence: 99%